Attenuated hypothalamic–pituitary–adrenal axis functioning predicts accelerated pubertal development in girls 1 year later. (August 2015) - Saxbe, Darby E.; Negriff, Sonya; Susman, Elizabeth J.; Trickett, Penelope K.
Abstract Accelerated pubertal development has been linked to adverse early environments and may heighten subsequent mental and physical health risks. Hypothalamic–pituitary–adrenal axis functioning has been posited as a mechanism whereby stress may affect pubertal development, but the literature lacks prospective tests of this mechanism. The current study assessed 277 youth (M = 10.84 years, SD = 1.14), 138 boys and 139 girls, who reported on their pubertal development and underwent the Trier Social Stress Test for Children at baseline and returned to the laboratory approximately 1 year later (M = 1.12 years, range = 0.59–1.98 years). For girls, lower cortisol area under the curve (with respect to ground) at Time 1 predicted more advanced pubertal development at Time 2, controlling for Time 1 pubertal development. This association persisted after additional covariates including age, body mass index, race, and maltreatment history were introduced, and was driven by adrenal rather than gonadal development. Cortisol was not linked to boys' subsequent pubertal development, and no interaction by gender or by maltreatment appeared. These results suggest that attenuated cortisol, reported in other studies of children exposed to early adversity, may contribute to accelerated pubertal tempo in girls.